Analytical analysis and heat transfer of CuO and MgO engine oil base nanofluid with the influence of dynamic viscosity, magnetic field, and convective boundary conditions - Rehman, Ali; Khun, Ma Chau; Rezapour, Shahram; İnç, Mustafa; Garalleh, Hakim A. L.; Muhammad, Taseer (Wiley-V C H Verlag Gmbh, 2024)
This research work investigates the semi-numerical analysis and heat transfer of MHD 2D, Copper Oxide, and Magnesium oxide engine oil base nanofluid with the consider effect of dynamic viscosity and convective boundary conditions (BCs). The convective BCs and the effect of dynamic viscosity on an extensible surface are considered by the flow system. We converted a set of PDEs into NODEs by applying the appropriate transformations. Using the HAM, we solve this dimensionless coupled equation one for temperature and other for velocity. The impact of various parameters for both temperature and velocity are demonstrated, such as the slip parameter, magnetic parameter (MP), Eckert number (EN), PN, and dynamic viscosity. In response to changes in developing factors, the flow features, such as temperature profiles (TPs) and velocity profiles (VPs), are analyzed and simulated using a physical description. The results of this study add to our knowledge of how engine oil-based nanofluids promote heat transmission and offer practical advice for thermal management and engineering applications.
Keywords: Transfer Enhancement; Thermal-Analysis; Flow; Performance; Stability